Development of Website-Based Statistical Learning Media at Bina Sarana Informatics Pontianak University - Adesfiana, Zeny Novia; Aunurrahman, Aunurrahman; Suratman, Dede; Sujaini, Herry; Karolina, Venny (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aims to design and evaluate the effectiveness of website-based statistical learning media at Bina Sarana Informatika University, Pontianak. The media was developed using Lectora Inspire by following the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The method applied in this study is research and development (R&D). The results of empirical tests conducted on students indicate that website-based statistical learning media is classified as adequate. The effectiveness measurement was carried out using the N-gain test, where the mean value obtained was 0.7679 or 76.79%. This means there was an increase of 76.79% in student understanding after using this media. Of the 100 students tested, 85 significantly increased understanding, with an average of 38.33 points between the pretest and posttest. These results place the effectiveness of learning media in the high category, indicating that this Media is efficacious in improving student learning outcomes. The results of this study indicate that website-based learning media designed with the ADDIE model can effectively improve students' understanding. This means that other educational institutions that want to improve the quality of their learning can adopt a similar approach, especially in subjects that require deep conceptual and analytical understanding, such as statistics.